2005
DOI: 10.1016/j.jasms.2005.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of 3,5,3′-triiodothyronine and 3,3′,5′-triiodothyronine by electrospray ionization tandem mass spectrometry

Abstract: A novel and rapid method for identifying and quantifying 3,5,3=-triiodothyronine (T3) and 3,3=,5=-triiodothyronine (rT3; reverse T3) has been introduced using electrospray ionization tandem mass spectrometry (ESI-MS/MS). MS 2 spectra in either negative ionization mode or positive ionization mode can be used to differentiate T3 and rT3. Quantification of the T3 and rT3 isomers under the negative ionization mode is also achieved without prior separation by HPLC. (J Am Soc Mass Spectrom 2005, 16, 1781-1786

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…However, the relative abundance of m/z 507.9 from T3 was lower than that from rT3, and the relative abundance of m/z 381.8 in 3,5-T2 was lower than that from 3,3’-T2. The mass spectrometric characteristics of the two T3 isomers and the two T2 isomers in this study are similar to previous observations [38, 39]. Also interesting to note, when CE values increased from 20 v to 35 v, m/z 478.7, [M+H-CIO 2 ] + , became the second most abundant fragment ion for T3.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the relative abundance of m/z 507.9 from T3 was lower than that from rT3, and the relative abundance of m/z 381.8 in 3,5-T2 was lower than that from 3,3’-T2. The mass spectrometric characteristics of the two T3 isomers and the two T2 isomers in this study are similar to previous observations [38, 39]. Also interesting to note, when CE values increased from 20 v to 35 v, m/z 478.7, [M+H-CIO 2 ] + , became the second most abundant fragment ion for T3.…”
Section: Resultssupporting
confidence: 90%
“…This phenomenon was also observed in previous studies [38, 39]. From chemical structures of these isomers (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A recently developed methodology shows that electrospray ionization tandem mass spectrometry (ESI‐MS/MS) can be used for identification and quantification of mixtures of isomers, such as chondroitin sulfate disaccharides, diastereomeric hexosamine monosaccharides, and diastereomeric N ‐acetylhexosamines isomers 19–21. Moreover, we have also demonstrated that ESI‐MS/MS can be used to identify and quantify T3 and rT3 isomers in mixtures 22. However, systematic investigation of T2 isomers and quantification of these compounds in mixtures based on the relative abundance of fragment ions in MS 2 spectra has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…A novel on-line HPLC system incorporating the high-performance frontal analysis (HPFA) system and electrochemical detection is developed for the simultaneous determination of unbound T 4 , T 3 , and rT 3 in human plasma [35]. Zhang et al [36] developed an ESI tandem mass spectrometry (MS/MS) technique both in positive and negative ion modes to distinguish and quantify T 3 and rT 3 by utilizing the difference in percent ion contributions of the MS/MS fragment ions. In this work, the relative molar percentages of T 3 and rT 3 isomers in a mixture were determined using a system of two equations.…”
mentioning
confidence: 99%